Blended Learning During Pandemic: EFL Undergraduate Students’ Satisfaction - Ni Wayan Tasya Astri Prawisanthi; I Gede Yoga Permana (Cetta: Jurnal Ilmu Pendidikan, 2022)
The objective of this research is to investigate the EFL students’ satisfaction on the implementation of blended learning at STKIP Agama Hindu Singaraja This research is a quantitative survey. The sample of this research was 76 undergraduate students of English education department STKIP Agama Hindu Singaraja. The data were gathered by using 5-point Likert scale questionnaire. The questionnaire validity and reliability checked and showed that the questionnaire was valid and had a high reliablity.  The data were analysed by using quantitative with SPSS program. The findings showed that students were very saisfied toward the implementation of blended learning (M=4.03, SD=.759). In conclusion, blended learning could be implemented in today’s Covid-19 pandemic situation as it provides more opportunity for students to engage in learning process.